Proceedings of 2013 Kaon Physics International Conference — PoS(KAON13) 2013
DOI: 10.22323/1.181.0010
|View full text |Cite
|
Sign up to set email alerts
|

New Physics Signatures in Kaon Decays

Abstract: Kaon physics provides a unique opportunity to identify new flavour and CP violating interactions beyond the Standard Model (SM). In the SM, implied by the hierarchical structure of the CKM matrix and the GIM mechanism, flavour changing neutral current processes are most strongly suppressed in the kaon sector while the suppression is much less effective in the B meson systems. Thus their theoretical cleanness makes rare K decays, in particular the K → πνν system, extremely well suited to look for deviations fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…In particular in [288] the status of NP contributions as of 2008 has been reviewed. A recent short review of NP signatures in Kaon decays can be found in [292].…”
Section: Preliminariesmentioning
confidence: 99%
“…In particular in [288] the status of NP contributions as of 2008 has been reviewed. A recent short review of NP signatures in Kaon decays can be found in [292].…”
Section: Preliminariesmentioning
confidence: 99%
“…Note that in the SM the sign of X(x t ) is positive. Recalling the relation Reλ 17) accurate to λ 4 terms, and solving for β then gives…”
Section: Jhep11(2015)033mentioning
confidence: 99%
“…Moreover, extensive calculations of isospin breaking effects and non-perturbative effects have been performed [10,11]. Reviews of these two decays can be found in [12][13][14][15][16][17][18] and their power in probing energy scales as high as several hundreds of TeV has been demonstrated in [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, once the CKM parameters |V cb |, |V ub | and γ will be precisely determined in tree-level decays, these two decays will offer excellent tests of the SM and constitute very powerful probes of NP. Reviews of these two decays can be found in [1,[76][77][78][79]. In particular in [80] bounds on K → πνν decays in correlation with the unitarity triangle and sin 2β within models with minimal flavour violation have been derived.…”
mentioning
confidence: 99%